2011
DOI: 10.1038/nsmb.2187
|View full text |Cite
|
Sign up to set email alerts
|

Tel1ATM and Rad3ATR kinases promote Ccq1-Est1 interaction to maintain telomeres in fission yeast

Abstract: SUMMARY The shelterin complex plays both positive and negative roles in telomerase regulation. While shelterin prevents the checkpoint kinases ATM and ATR from fully activating DNA damage responses at telomeres, those kinases are also required for telomere maintenance. In fission yeast, cells lacking both Tel1 (ATM ortholog) and Rad3 (ATR ortholog) fail to recruit telomerase to telomeres, and survive by circularizing chromosomes. However, the critical telomere substrate(s) of Tel1ATM/Rad3ATR remained unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
182
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(202 citation statements)
references
References 41 publications
20
182
0
Order By: Relevance
“…4D). We reasoned that the different behavior of ccq1D and ccq1-T93A is because Ccq1 is also part of the SHREC complex involved in telomere silencing (Sugiyama et al 2007; Motamedi et al 2008), which is not affected by the ccq1-T93A mutation (Moser et al 2011;Yamazaki et al 2012). Consistent with this idea, we also found that sde2D, which resulted in selective loss of telomere silencing (SugiokaSugiyama and Sugiyama 2011), was able to bypass RNAi for pericentric heterochromatin formation (Supplemental Table S1; Fig.…”
Section: Elimination Of Other Shelterin Components Also Bypasses Rnaisupporting
confidence: 75%
See 2 more Smart Citations
“…4D). We reasoned that the different behavior of ccq1D and ccq1-T93A is because Ccq1 is also part of the SHREC complex involved in telomere silencing (Sugiyama et al 2007; Motamedi et al 2008), which is not affected by the ccq1-T93A mutation (Moser et al 2011;Yamazaki et al 2012). Consistent with this idea, we also found that sde2D, which resulted in selective loss of telomere silencing (SugiokaSugiyama and Sugiyama 2011), was able to bypass RNAi for pericentric heterochromatin formation (Supplemental Table S1; Fig.…”
Section: Elimination Of Other Shelterin Components Also Bypasses Rnaisupporting
confidence: 75%
“…Rap1 and Poz1 form a bridge that connects Taz1 and Pot1-Tpz1 complexes (Miyoshi et al 2008). Pot1-Tpz1 associates with Ccq1 to recruit telomerase Trt1, which uses associated RNA as a template to elongate the telomere overhang (Nakamura et al 1997;Miyoshi et al 2008;Tomita and Cooper 2008;Moser et al 2011;Yamazaki et al 2012). By ChIP analyses, we found that Poz1 was enriched at telomeres, as expected, but not detected at pericentric repeats, even in dcr1D cells (Fig.…”
Section: Elimination Of Other Shelterin Components Also Bypasses Rnaisupporting
confidence: 49%
See 1 more Smart Citation
“…Importantly, S. pombe Tel1 (ortholog of mammalian Atm) and Rad3 (ortholog of mammalian Atr) promote the direct interaction between Ccq1 and the Est1 subunit of telomerase (Moser et al 2011;Yamazaki et al 2012). Ccq1 is phosphorylated on T93 by Tel1 and Rad3, and mutation of this site abolishes telomerase recruitment.…”
Section: S Pombementioning
confidence: 99%
“…Whereas Taz1 binds to double-stranded G-rich telomeric repeats, Pot1 binds to 3′ single-stranded overhang telomeric DNA, known as G-tails (8,9). Rap1, Poz1, and Tpz1 act as a molecular bridge connecting Taz1 and Pot1 through protein-protein interactions (7), and Ccq1 contributes to telomerase recruitment via Rad3 ATR /Tel1 ATM -dependent interaction with the telomerase regulatory subunit Est1 (10).…”
mentioning
confidence: 99%